Mobility and the making of the neoliberal "creative city": The streetcar as a creative city project?. (January 2017) - Culver, Gregg
Abstract: In recent years, there has been a remarkable rebirth of the streetcar in cities throughout the United States, with dozens of projects under consideration, in planning and construction, or already completed in cities throughout the country. Building on transport geography research on the streetcar, urban studies contributions on neoliberal urbanization and the creative city, and insights from the new mobilities paradigm, this paper sets out to investigate the broad political − economic logic driving this nationwide development trend. Based predominantly on a qualitative content analysis of selected project documents from 12 streetcar projects, I find that the reemergence of these streetcar projects in recent years reflects and is embedded in the general trajectory of neoliberal urbanization and can more precisely be understood as a creative city development tool. Highlights: Investigates the political − economic logic driving the return of the streetcar to US cities Examines 12 streetcar projects' key documents in 11 US cities using qualitative content analysis Finds that the streetcar can be understood as a neoliberal, "creative city" development tool Suggests the politics of streetcar development as a productive area of future research